(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Glutathione S-transferases (GSTs) are enzymes of Phase II, which play an important role in cellular detoxification by conjugation of reduced glutathione with a wide variety of potentially toxic and carcinogenic. Polymorphisms of genes coding for the glutathione S-transferase (GST) enzymes were known to be associated with susceptibility to various forms of cancer, or outcome of multichemotherapeutic regimens. Objective:To analyze of the frequencies of the major polymorphisms of the GSTM1 and GSTT1 in Baghdad population to provide a basic database for future genetic and clinical studies. Methods: Peripheral blood was obtained from 142 healthy individuals randomly selected from two districts in Baghdad. The age of studied participants ranges from 15-46 yeares at time of inclusion. Genomic DNA was isolated from leukocytes using Wizerd genomic DNA purification kit. The GSTT1 and GSTM1 gene polymorphism were evaluated using multiplex polymerease chain reaction in which albumen gene was used as internal controls. Results:Twenty nine individuals (20.4%) revealed no amplification of the GSTT1 gene (null type). The null GSTM1 genotype was found in 66.2% (94 individuals). Twelve percent (17/142) had null genotype for both genes. The most frequently observed genotype was GSTT1 positive/GSTM1 null genotype (54.2%) while the GSTT1 null/GSTM1 positive genotype observed in 12 individuals (8.5%). GSTT1postive/GSTM1 positive genotype was found in 36 (25.4%) of the sample study. Conclusion:Data of the present study showed that the frequency of GSTT1 and GSTM1null genotype of the sample study is in concordance with those documented for Caucasian, Asians, and Arabs population. This study provides information for frequency distribution of GSTT1and GSTM1 null genotypes in the Baghdad population and information about genetic difference between Iraqi individuals and other population that provide basis for future genetics and clinical studies. Keywords: glutathione S-transferase, polymorphisms